Assessment of thyroid dysfunction, dyslipidemia and oxidative stress in hypertensive end stage chronic renal disease patients in a teaching hospital in Western Uttar Pradesh - Kachhawa, Poonam; Sinha, Vivek (Asian Journal of Medical Sciences, 2019)
Background: CKD is a serious health problem in worldwide. In developing nation, CKD has severe implication on health and economic output. The rapid increase of common risk factors such as hypertension (HTN), obesity and type 2 diabetes will result in greater and more burdens to developing country. There are many complications associated with CKD including thyroid dysfunction, dyslipidemia,hypertension and cardiovascular disease (CVD).It is generally seen that patients suffering from CKD are at high risk of cardiovascular disease. Aims and Objectives: The purpose of the study was to evaluate the diagnostic screening of thyroid dysfunction, dyslipidemia and oxidative stress in hypertensive end stage chronic renal disease patients. Materials and Methods: Thyroid status, Lipid profile, serum Urea, serum Creatinine, serum Uric acid, serum electrolyte, Catalase,Malondialdehyde (MDA) and Superoxide dismutase (SOD) were assayed in 160 subjects in which 80 patients of CKD were having hypertension and 80 healthy controls. Results: In our study, we found statistical significantly increased level of (p<0.001) of malondialdehyde (MDA) and significantly decreased level (p<0.001) of Catalase and Superoxide dismutase (SOD).There was found significantly increased level (p<0.001) of TSH in CKD associated with hypertension patients.We also found deranged lipid profile and renal functions in CKD associated with hypertension patients as compared to controls. Conclusion: In the present study, we arrived at conclusion that dyslipidemia and thyroid dysfunction is very common in CKD patients. Our study revealed that there was significant association between thyroid dysfunction and CKD progression and dyslipidemia. The antioxidant status is assessed through changes in antioxidant enzymatic activity in patients of CKD with hypertensive and data provide evidence of blood pressure modulation by measurable oxidative stress–related parameters.